Assessment of Adaptive Functioning Skills of Children Living in Foster Care in Ogbomoso North, Oyo State - AGARRY, Rachael Ojima; OLANIYI, Sheriff Adekunle; ABDULLAHI, Abubakar (Ilorin Journal of Education, 2025)
Adaptive functioning develops throughout early childhood, and its inadequacy implies that the child has developmental, emotional, or disability problems. This study, therefore, assessed the adaptive functioning skills of children living in foster care in Ogbomoso North, Oyo State. The study raised three research questions and a descriptive survey research design was adopted. A purposive sampling procedure was used to select twenty-five (25) children living in foster care in Ogbomoso North, Oyo State. The instrument for the study was a researcher designed rating scale titled ‘‘Adaptive Functioning Skills of Children Living in Foster Care Rating Scale’’. The face and content validity of the instrument was validated by experts from the Department of Adult and Primary Education. The Reliability was assessed using the test-retest method, yielding a reliability coefficient of 0.75. Data analysis involved using Mean and standard deviation to analyze all the research questions. The findings of the study discovered that children living in foster care in Ogbomoso North Local Government Area generally possess well-developed adaptive functioning skills. It was however recommended among others that foster care management should teach social interaction skills through role-playing and group activities to enhance communication, empathy, and relationship-building.